Productivity Improvement Knuckle Steering Production Line through the Objective Matrix (OMAX) Method - Mukhtar, M Nushron Ali; Prihono; Hermawan, Moch Amaludin (UNIPA PRESS, 2026)
In the face of market dynamics and increasing demand, the company needs to optimise productivity in every production line, including the knuckle steering item line. This study aims to measure and evaluate productivity using the Objective Matrix (OMAX) method, which integrates several key performance ratios. The analysis results showed that the highest productivity occurred in March 2024 (517.2), while the lowest was in September 2024 (23.6). The lowest ratio was production achievement to machine capacity, contributing only 27 out of a total score of 131. The low productivity is due to the lack of operator competence, suboptimal machine maintenance, long process duration, and the high amount of defective material from the foundry process. These findings emphasise the importance of comprehensive improvements in human resources, machine maintenance, and raw material quality control to drive sustainable productivity improvements.